Severity of Vessel Color Changes and Macular and Peripheral Whitening in Malarial Retinopathy Are Associated with Higher Total Body and Sequestered Parasite Burdens - Chiadika Nwanze; Daniel Muller; Priscilla Suleman; Mrinmayee Takle; John R. Barber; Kyle J. Wilson; Nicholas A. V. Beare; Karl B. Seydel; Douglas G. Postels (Tropical Medicine and Infectious Disease)
Two-thirds of children with cerebral malaria (CM) exhibit retinopathy characterized by whitening, vessel color changes, and/or hemorrhages. The pathogenesis of malarial retinopathy is not fully understood. This study aimed to assess the relationship between malarial retinopathy and the severity of its components (macular whitening, retinal hemorrhages, and vessel color changes) with the total, circulating, or sequestered parasite load in children with CM. Total parasite burden was estimated by measuring plasma levels of Plasmodium falciparum histidine-rich protein 2 (PfHRP2), while the sequestered load was calculated as the difference between the total burden and circulating parasitemia. Children with retinopathy-positive CM (n = 172) had higher total and sequestered parasite burdens compared to retinopathy-negative children (n = 42) (both p = 0.049). In a subgroup with detailed retinopathy grading (n = 52), more extensive vessel color changes correlated with higher total, sequestered, and circulating parasite loads (p = 0.0057, p = 0.0068, and p = 0.0433, respectively). Peripheral retinal whitening was also associated with increased total and sequestered loads (p = 0.0017 and p = 0.0012). No association was found between retinal hemorrhages and parasite burden, indicating that other factors may influence their pathogenesis.